Pengaruh Daya Tarik Iklan dan Celebrity Endorser terhadap Keputusan Pembelian Konsumen pada Usaha Kecil Menengah (UKM) Produk Pakaian di Pineappleshopy Surabaya - Vilda, Septiana; Maduwinarti, Ayun; Pujianto, Agung (Universitas 17 Agustus 1945 Surabaya, 2021)
ABSTRACTPurchase decision is a process that consumers go through before buying a product where consumers evaluate a choice from two or more available alternative choices. Several factors that influence purchasing decisions are the attractiveness of advertisements and celebrity endorsers. This study aims to analyze and determine the effect of advertising attractiveness on purchasing decisions and the influence of celebrity endorsers on consumer purchasing decisions on clothing products SMEs Pineappleshopy Surabaya. The sampling technique in this study was using a questionnaire with a sample size of 100 respondents. The data obtained from the questionnaire was then processed and analyzed using multiple linear regression. The results of this study indicate that the attractiveness of advertisements and celebrity endorsers partially and simultaneously has a positive and significant effect on consumer purchasing decisions at SMEs for clothing products, Pineappleshopy Surabaya. Keywords: Advertising Attractiveness, Celebrity Endorser and Purchase Decision